2022
DOI: 10.3390/biomimetics7030111
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Mineralization of Tooth Enamel Using Nanocrystalline Hydroxyapatite under Various Dental Surface Pretreatment Conditions

Abstract: In this report, we demonstrated the formation of a biomimetic mineralizing layer obtained on the surface of dental enamel (biotemplate) using bioinspired nanocrystalline carbonate-substituted calcium hydroxyapatite (ncHAp), whose physical and chemical properties are closest to the natural apatite dental matrix, together with a complex of polyfunctional organic and polar amino acids. Using a set of structural, spectroscopy, and advanced microscopy techniques, we confirmed the formation of a nanosized ncHAp-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 68 publications
(133 reference statements)
0
16
0
Order By: Relevance
“…When used alone or in conjunction with a mouthwash that also contains hydroxyapatite, hydroxyapatite toothpaste is an efficient home treatment for tooth erosion in physically active people such as rugby players [ 95 , 96 ]. In several research, the pH of commercial beverages such as sports and energy drinks, water, fruit juices and beverages, soda, milk, tea, and coffee was measured using a pH meter [ 60 , 97 ]. Moreover, gravimetric analysis and the Vickers hardness tester were used to assess the effect of five highly acidic drinks on weight loss and surface hardness of human teeth samples [ 60 , 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When used alone or in conjunction with a mouthwash that also contains hydroxyapatite, hydroxyapatite toothpaste is an efficient home treatment for tooth erosion in physically active people such as rugby players [ 95 , 96 ]. In several research, the pH of commercial beverages such as sports and energy drinks, water, fruit juices and beverages, soda, milk, tea, and coffee was measured using a pH meter [ 60 , 97 ]. Moreover, gravimetric analysis and the Vickers hardness tester were used to assess the effect of five highly acidic drinks on weight loss and surface hardness of human teeth samples [ 60 , 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several research, the pH of commercial beverages such as sports and energy drinks, water, fruit juices and beverages, soda, milk, tea, and coffee was measured using a pH meter [ 60 , 97 ]. Moreover, gravimetric analysis and the Vickers hardness tester were used to assess the effect of five highly acidic drinks on weight loss and surface hardness of human teeth samples [ 60 , 97 , 98 ]. Sports and energy drinks, fruit juices, and carbonated soft drinks were in the most acidic beverage categories, considerably reducing enamel surface hardness owing to mineral loss [ 60 , 95 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of amino acids and alkalinization under given conditions should increase the hierarchical organization of the pretreated organomineral matrix of apatite [ 8 , 29 , 30 , 31 ]. Thus, in our previous work, it was shown that the pretreatment of enamel in the alkaline solution of Ca(OH) 2 and an amino acid booster, and the following mineralization performed with the use of hydroxyapatite (HAp), resulted in the formation of a mineralized layer with homogeneous micromorphology and presumable orientation of HAp nanocrystals [ 32 , 33 ]. The binding of hydroxyapatite nanocrystals with an amino acid complex resulted in a considerable increase (~15%) in the nanohardness value in the mineralized layer as compared with a similar value of the intact natural enamel.…”
Section: Introductionmentioning
confidence: 99%